TATA CARA DAN PENGELOLAAN WAKAF UANG DI INDONESIA (ZISWAF: Jurnal Zakat dan Wakaf, 2017)
Cash waqf is not refers to money waqf only but also cover waqf of capital stock and obligation. This kind of waqf has been acknowledged by waqf institution in Indonesia and also has been regulated by the government. This article describes its regulation and how to do cash waqf in Indonesia.